Pengaruh Influencer dan Diskon Harga serta Ulasan Pelanggan terhadap Keputusan Pembelian Produk Skincare Skintific di Samarinda - Alicia Nashira Sabita; Asnawati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the influence of influencers, price discounts, and customer reviews on the purchase decisions of Skintific products in Samarinda. A quantitative approach was applied using Partial Least Square (PLS) analysis with 112 respondents who have used Skintific products. The results indicate that influencers have no significant effect on purchase decisions. In contrast, price discounts show a positive and significant effect, while customer reviews are the strongest factor influencing purchasing decisions. These findings suggest that consumers are more driven by economic benefits and real user experiences rather than influencer promotions.